Successful use of reduced‐intensity conditioning and matched‐unrelated hematopoietic stem cell transplant in a child with Diamond‐Blackfan anemia and cirrhosis. (23rd June 2015) - Asquith, Justin M.; Copacia, Jessica; Mogul, Mark J.; Bajwa, Rajinder P. S.
Abstract For patients with DBA who are transfusion dependent, HSCT is the only cure. Chronic transfusions can lead to cirrhosis secondary to iron overload, making them poor candidates for myeloablative HSCT. RIC regimens are associated with lower morbidity and mortality compared to myeloablative regimens, but use of RIC in DBA has been limited. Here we present a 14‐yr‐old girl with DBA and multiple comorbidities including liver cirrhosis, who underwent MUD HSCT utilizing a RIC regimen that is novel to this condition. She tolerated the regimen well, and at 21 months, she remains transfusion independent with chimerisms at 99%.